Review of hydraulic seal failures due to effect of medium to high temperature. (September 2021) - Mahankar, Prasanna S.; Dhoble, Ashwinkumar S.
Highlights: Effect of temperature on various modes of hydraulic seal failure. Insights to various thermal aging phenomenon which causes a hydraulic seal failure. Study of thermal aging experiments. Summarization of change in the mechanical properties of hydraulic seal during thermal aging. Abstract: Hydraulic seal, generally made up of elastomers, is used in hydraulic systems to prevent the leakage and facilitate the efficient transmission of fluid power into mechanical power. Most of the industries dealing with fluid power consider hydraulic seal as a one of the important components. Seal failure during the operation may cause a complete shutdown of the system, downtime in production line and affect the quality of the products. Since the cost of the seal is less, replacement of seals is generally preferred when seal failure occurs. Most of the time, engineering aspects of seal failure is not considered. Understanding of seal failure mechanisms can improve the reliability of operation, life, and design of the seal. Apart from functional failure, a thermal aging phenomenon like swelling, rapid gas decompression (RGD), change in crosslink density, chain scission reaction, and wear process worsens the mechanical and chemical properties of the seal. These mechanisms can cause seal failure and are strongly governed by temperature in the sealing region. This paper explains the failure mechanism of hydraulic seal. The objective of paper is to provide a review on influence of medium to high temperature on seal failure mechanism and provide insights to improve seal performance and reliability.